Attitude towards patient undergraduate medical students in the University of Malaya / Jeevitha Rajasingam - Rajasingam, Jeevitha (2020)
In the last two decades, patient safety awareness has become one of the emerging themes. To prevent from doing harm to patients, safe medical practices should be implemented and followed strictly. Therefore, a basic understanding of human factor principles need to be instilled into all health care workers. Medical universities play a vital role in fostering patient safety attitudes of their students towards the importance of patient safety during their practise. However, the medical curricula still face challenges regarding the correct timing and appropriate methods of instruction in their understanding of their principles. Experiments have shown that patient safety classes in health care facilities are being developed, incorporated, and tested. In this study, the attitude towards patient safety among medical students in University of Malaya was studied. The end results of this study would help medical schools in introducing patient safety components to their curriculum. This study was performed among undergraduate medical students in the University of Malaya. Attitudes toward Patient Safety Questionnaire III (APSQ-III) - a 30- items, 5-point Likert scale questionnaire, was used as the study instrument. Year 1 to Year 5 medical students were approached via an online questionnaire using Google form and administered to their email addresses. It resulted in a positive attitude culture towards patient safety among the undergraduate medical students. By measurements, the attitude towards implementing team functioning was scored the highest (mean=4.37) and the male medical students had better attitude towards Error Reporting (mean=3.66) compared to the females. For Working hours, the scores (mean=4.03) among the Year 1 medical students was the lowest compared to all the other years. Students had positive views of patient safety importance, some still felt that patient safety must be highlighted further in the medical curriculum. The World Health iv Organisation (WHO) has since established the Patient Safety Curriculum Guide to support health care organizations who incorporate values of patient protection by concentrating on operating a safety culture for all health care professionals and undergraduate medical students in an integrated manner. Hence more studies are needed to be focused in curriculum to enhance the attitude of students towards patient safety.